2011
DOI: 10.1111/j.1471-4159.2010.07015.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular prion protein is implicated in the regulation of local Ca2+ movements in cerebellar granule neurons

Abstract: 1These authors contributed equally to this study.Abbreviations used: AEQ, aequorin; BSA, bovine serum albumin; CGN, cerebellar granule neurons; CH1, immunoglobulin heavy chain constant region 1; ER, endoplasmic reticulum; GFAP, glial fibrillary acidic protein; HA, hemagglutinin; IB, isolation buffer; KO, knock-out; KRB, Krebs-Ringer buffer; lsCSQ, leader sequence of calsequestrin; mAb, monoclonal antibody; pAb, polyclonal antibody; PBS, phosphatebuffered saline; PM, plasma membrane; PMCA, plasma membrane Ca 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…Interestingly, it has been described that PrP C mediates neuronal iron uptake and transport, which is important to keep the brain in working order (Singh et al 2009). It was also reported that PrP C has a high expression at synapses and that it was involved in the homeostasis of Ca 2C of cerebellar granule neurons (Lazzari et al 2011). It can bind copper as well for an antioxidant activity, which, in turn, might have vital implications for synaptic homeostasis (Brown 2001).…”
Section: Prion Protein In Brain and Muscle Stem Cell Regenerationmentioning
confidence: 98%
“…Interestingly, it has been described that PrP C mediates neuronal iron uptake and transport, which is important to keep the brain in working order (Singh et al 2009). It was also reported that PrP C has a high expression at synapses and that it was involved in the homeostasis of Ca 2C of cerebellar granule neurons (Lazzari et al 2011). It can bind copper as well for an antioxidant activity, which, in turn, might have vital implications for synaptic homeostasis (Brown 2001).…”
Section: Prion Protein In Brain and Muscle Stem Cell Regenerationmentioning
confidence: 98%
“…The ER-Aeq Ca 2+ probe was described in [40]. For generation of the CathD-Aeq Ca 2+ probe a fragment of the cathepsin D (CathD) cDNA was first amplified using the following primers: Forward: 5 -ggaagcttgaattcgccaccatgcagccctccag-3 Reverse: 5 -ggaagcttgagggtcttcccggcctgcgacacct-3 which caused the addition of a HindIII site in the 5 non-coding region and downstream the lysosomal targeting sequence of the CathD cDNA, but not the catalytic region [41].…”
Section: Generation Of Cathd-aeq Ca 2+ Probe and Aequorin Ca 2+ Measumentioning
confidence: 99%
“…As a consequence, the loss of its function, during disease progression, may contribute to Ca 2+ derangement and synaptic failure. 110 Even though astrocytes were described to be the earliest site of PrP Sc accumulation in brain, 111 no information is currently available on the Ca 2+ signaling of scrapie-infected astroglia. The presence of chronically activated glial cells around PrP Sc depositions is a well documented feature in prion diseases.…”
Section: Prion Diseasesmentioning
confidence: 99%